Multilingual Selves: Exploring Language Ideologies and Linguistic Repertoires among Young People in Cape Town - Adams, Imrah (Linguistics, 2024)
Against the backdrop of a (provincial) language policy that includes Afrikaans, English, and isiXhosa, this project investigates the language ideologies and language practices of a group of young people who live in a historically Afrikaans-speaking area in the Northern Suburbs of Cape Town. More broadly, this study seeks to understand the multilingualism of individual speakers within their social location while, at the same time, giving recognition to their personal experiences with language. The data collected is qualitative in nature, consisting of in-depth interviews, language portraits, and focus group discussions. In total, eleven different participants were involved in this study and were recruited via school visits and through word of mouth. Six of these participants, namely, Jaco, Claire, Farzahna, Rachel, Zene, and Kayla participated in all three data collection activities. Jason, Porcia, Mikayla participated with the interviews and the language portrait. Zonita participated in the focus group and the language portrait. Finally, Jake participated in the focus group, but did not complete the task and left the research process. The results confirm the expected high esteem of English, with ideologies focused on global communication, its lingua franca nature within South Africa, and the ways in which English is linked to travel prospects and globalization. Yet, all participants are all multilingual, and also speak or encounter Afrikaans in the home. They describe Afrikaans as having many varieties, standard and non-standard. Standard Afrikaans is associated mostly with negative experiences, including cases of judgment and unease. In contrast, non-standard varieties, referred to as Kaaps in the recent scholarly literature, are discussed as constituting a linguistic home, and as establishing a connection to family and friends. The results from the interviews and focus groups also indicate that isiXhosa and other indigenous African languages are frequently erased, both discursively and practically. At times, the languages within the participants' repertoires were racialized: English is portrayed as a language for all, Standard Afrikaans is associated with whiteness, non-standard Afrikaans with coloured identities, and isiXhosa with black African speakers. Furthermore, participants articulate a desire for foreign languages such as French, Japanese, and Russian. This was explored through language portraits, which helped to foreground participants' lived experiences, and which also brought African languages more strongly into focus